Alienation, Exploitation, and Social Media - Rey, P J (The American behavioral scientist (Beverly Hills), 2012)
This article is a critical examination of how capitalism has adapted to the explosion of websites devoted to user-generated content (commonly referred to as social media or Web 2.0). The author proceeds by reviewing how Marx applies the concepts of alienation and exploitation to his paradigmatic example (i.e., the factory); the author then attempts to extend the logic of both concepts to determine what they might reveal about the structural conditions of social media. A difference of prime importance between the two case studies is that factory work is wage labor coerced by economic necessity, whereas use of social networking sites is apparently voluntary and done freely. The author concludes by arguing that social media users are subject to levels of exploitation relatively consistent with industrial capitalism, whereas the structural conditions of the digital economy link profitability to a reduction in the intensity of alienation. Finally, he infers that social media is not economically beneficial to most users.